#### Answer

$3$

#### Work Step by Step

$\log _{\left( x+3\right) }6=1\Rightarrow \left( x+3\right) ^{1}=6\Rightarrow x+3=6\Rightarrow x=3$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$3$

$\log _{\left( x+3\right) }6=1\Rightarrow \left( x+3\right) ^{1}=6\Rightarrow x+3=6\Rightarrow x=3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.